Prediction of burst pressure on steel pipes using Gurson-Tvergaard-Needleman (GTN) model - Kim Sung, Chong (2013)
A micromechanical model of ductile fracture is applied for API X65 steel to predict ductile failure of a full-scale API X65 pipes with simulated corrosion and defects under internal pressure. The micromechanical model is the Gurson model, incorporating void nucleation, growth and coalescence where the burst pressure is predicted based on the critical void volume fraction.The present study involves experimental comparison and numerical studies of the burst pressure of pipe under ductile fracture. The main objective of the present study is to determine the burst pressure of steel pipe using GursonTevaagard model. For the experimental, the results are from the previous research journal. For the finite element analysis, the pipe model is modeled as a 3 dimensional, quarter-model in MSC.PATRAN with MSC.MARC as nonlinear implicit solver. Results with proposed ductile fracture model indicates that predicted failure pressure attain maximum load for all cases, and are in good agreement with experimental data. It also showed that the burst pressure is decreasing for increasing defect depth and length. For the characters of void volume fraction, f, it can be seen that once the void reach void growth, it soon come to void coalescence, where the burst pressures are predicted at critical void and then fracture. The results from gouge defect varies in length is analyze based on the equivalent plastic strain, and the stress triaxially,  where void growth dependent on this two key quantities. Void volume fraction are examined based on the equivalent plastic strain and stress triaxiality on the normalize distance along the defect length and depth. It is found that distribution of equivalent plastic strain agreed well with the void volume fraction and the critical point occur at the defect tip along the defect depth and length.